Comparing measures of citizen trust and user satisfactionas indicators of `good governance': difficulties in linking trust and satisfaction indicators - Bouckaert, Geert; Walle, Steven Vande (2003)
Until recently, public administration mainly used so-called `hard indicators', such as resources and outputs, to monitor performance. Increased attention on accountability and issues around impacts and outcomes have stimulated the introduction of `soft' indicators - e.g. citizen and user satisfaction targets. Moreover, there is increased demand for information on performance in relation to `governance' as a whole, including `quality of life' indicators. Politicians, journalists and citizens increasingly express their worries about a decreasing level of trust in government and the detrimental effects this has on government and on the cohesion of society - they appear to assume that more trust and more satisfaction equal better governance. Increasing the quality of governance will thus also lead to citizens who are more satisfied and more trusting. This article shows that current attempts to measure trust and satisfaction in government are misleading if they claim to be measuring trust and satisfaction in government are misleading if they claim to be measuring good governance for two reasons. First, satisfaction is difficult to measure and very service-specific. Second, trust in government is easier to measure but its linkages with good governance are far from clear. Even when trust in government can be measured, it is not at all clear whether changes in the level of trust are actually influenced by government-related factors. We suggest, finally, the hypothesis that trust could be insufficient but necessarily part of a set of indicators which are unnecessary but sufficient for good governance. - Reproduced.
Keywords: Public administration; Good governance